2012
DOI: 10.1002/jmv.23306
|View full text |Cite
|
Sign up to set email alerts
|

Rhinovirus load and disease severity in children with lower respiratory tract infections

Abstract: It has not been clarified if there is a correlation between rhinovirus (RV) load and disease severity in the lower respiratory tract infections of hospitalized children. This study was undertaken to elucidate the contribution of the viral load to the development of disease severity in 412 children ≤3 years of age who were hospitalized with lower respiratory tract infections. The RV load in nasopharyngeal aspirates obtained from the patients at the time of admission was measured by real-time quantitative revers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
3
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 41 publications
1
24
3
3
Order By: Relevance
“…In our previous study, we found that HRV infection was associated with asthma in our region . Some authors have demonstrated a close correlation between the HRV viral load and the disease severity in children with lower respiratory tract infections . However, there have been no reports on the correlation of the viral load of different HRV species with the severity of asthma exacerbations.…”
Section: Introductionmentioning
confidence: 54%
“…In our previous study, we found that HRV infection was associated with asthma in our region . Some authors have demonstrated a close correlation between the HRV viral load and the disease severity in children with lower respiratory tract infections . However, there have been no reports on the correlation of the viral load of different HRV species with the severity of asthma exacerbations.…”
Section: Introductionmentioning
confidence: 54%
“…There is a positive, albeit loose, relationship between RV virus load and clinical symptoms, 40, 41 and virus-induced cytokines, chemokines, and interferons may also contribute to respiratory symptoms. 4245 We demonstrated that RV-B types induce lower quantities of pro-inflammatory cytokines, which also could lead to milder illness.…”
Section: Discussionmentioning
confidence: 99%
“…The literature on the relation between disease severity and viral load is conflicting. Some investigators suggest a positive relationship [6][7][8][9][10][11][12][13][14][15], although others cannot confirm these results [16][17][18][19][20]. Multiple viruses are detected rather frequently in children with respiratory infections and in these cases it is almost impossible to determine the causative pathogen and the relation between viral load and disease severity [21][22][23].…”
mentioning
confidence: 99%